Security policy specification for home network. (25th September 2009) - Kim, Geon Woo; Lee, Deok Gyu; Han, Jong Wook; Kim, Sang Wook
As home network is expanding into ubiquitous computing environment and numerous home network services are available, we need to protect home network system from illegal accesses and a variety of threats. Home network is exposed to various cyber attacks of internet, involving hacking, malicious codes, worms, viruses, DoS attacks, and eavesdropping since it is connected to internet. So in this paper, we propose a new specification for security policy on home network for guaranteeing reliability and availability including authentication, authorisation and security policy deployment.